MEDIA PEMBELAJARAN: DARI KONSEPSI KE UTILISASI DAN PERMASALAHANNYA - M. Miftah (Balai Besar Guru Penggerak Jawa Timur, 2015)
The importance of the position / function of the media as an integral part of learning, it is important to get the attention of the teacher. Therefore, teachers should not only understand the concept of learning media, the type / variety, criteria and procedures as well as the election process, but also on the principle of utilization and possible problems. Media so that learning can be planned and used in an integrated and precise in learning activities, then in this paper will discuss criteria for the selection of media and the steps, use of media and the possibility of various problems to be faced. Some criteria for media selection are (1) compliance with the learning objectives to be achieved, (2) support the subject matter to be discussed, (3) practical, flexible, and easy to be used, (4) in accordance with the knowledge and skills of teachers to use it, ( 5) according to the characteristics and the number of goals that will use them (small, medium, or large), and (6) the quality or the technical quality of the type of media that will be used, (7) affordability of the financial capacity of the procurement, (8) the availability of instructional media needed in the market, and (9) is compatible with the device or the facilities available or already owned. AbstrakPentingnya kedudukan/fungsi media sebagai bagian integral dalam pembelajaran, perlu kiranya mendapatkan perhatian para guru. Oleh sebab itu, guru seyogianya tidak hanya memahami konsep tentang media pembelajaran, jenis/ragamnya, kriteria dan prosedur serta proses pemilihannya, tetapi juga mengenai prinsip pemanfaatannya dan kemungkinan permasalahan yang terjadi. Agar media pembelajaran dapat direncanakan dan dimanfaatkan secara terpadu dan tepat di dalam kegiatan pembelajaran, maka di dalam tulisan ini akan dibahas kriteria pemilihan media dan langkah-langkahnya, pemanfaatan media dan kemungkinan berbagai permasalahan yang akan dihadapi. Beberapa kriteria pemilihan media adalah: (1) kesesuaian dengan tujuan pembelajaran yang ingin dicapai, (2) mendukung materi pelajaran yang akan dibahas, (3) praktis, luwes, dan mudah dimanfaatkan, (4) sesuai dengan pengetahuan dan keterampilan guru untuk memanfaatkannya, (5) sesuai dengan karakteristik dan jumlah sasaran yang akan memanfaatkannya (kelompok kecil, sedang, atau besar), dan (6) mutu atau kualitas teknis jenis media yang akan dimanfaatkan, (7) keterjangkuan kemampuan finansial untuk pengadaannya, (8) ketersediaan media pembelajaran yang dibutuhkan di pasaran, dan (9) kompatibel dengan perangkat atau fasilitas yang tersedia atau yang telah dimiliki.